2001
DOI: 10.1074/jbc.m102008200
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Induces Serine Phosphorylation of the Adaptor Protein p66Shc and Its Association with 14-3-3 Protein in Glomerular Mesangial Cells

Abstract: Endothelin-1 (ET-1) is a vasoconstrictor peptide known to be a potent mitogen for glomerular mesangial cells (GMC).Shc resulted in its association with the serine binding motif-containing protein 14-3-3. ET-1-induced phosphorylation of a serine encompassed in the 14-3-3 binding motif of p66Shc was confirmed in experiments employing anti-phospho-14-3-3 binding motif antibodies. These studies are the first to demonstrate that G protein-coupled receptors stimulate serine phosphorylation of p66Shc and the first to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
0
38
1
Order By: Relevance
“…Accordingly, in this study, overexpression of a phosphorylation-defective p66 Shc mutant protein in INS-1E cells did not affect basal and reduced palmitate-induced apoptosis, respectively. Depending on the cellular context and stimulus, Ser 36 phosphorylation of p66 Shc was found to be promoted by either the MAP kinases ERK-1/2 or the stressactivated kinases JNK and p38 MAPK [14,15,35,[38][39][40][41][42]. In specific cells, it was shown to be mediated by PKCβ activation [43][44][45].…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, in this study, overexpression of a phosphorylation-defective p66 Shc mutant protein in INS-1E cells did not affect basal and reduced palmitate-induced apoptosis, respectively. Depending on the cellular context and stimulus, Ser 36 phosphorylation of p66 Shc was found to be promoted by either the MAP kinases ERK-1/2 or the stressactivated kinases JNK and p38 MAPK [14,15,35,[38][39][40][41][42]. In specific cells, it was shown to be mediated by PKCβ activation [43][44][45].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several groups, including ours, have reported serine phosphorylation of the p66 Shc isoform induced by various extracellular stimuli such as growth factors and TPA (19), hydrogen peroxide and UV irradiation (20), Taxol (21), and endothelin-1 (22). In this work, we identified three serine/threonine phosphorylation sites in p66 Shc (20) and appears to be the main phosphorylation site in this isoform.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to tyrosine phosphorylation, p66 Shc can also be phosphorylated at serine/threonine residues in response to epidermal growth factor (EGF) (18), 12-O-tetradecanoylphorbol-13-acetate (TPA) (19), UV stress (20), Taxol (21), and endothelin-1 (22). EGF-induced serine/threonine phosphorylation of p66…”
mentioning
confidence: 99%
“…In fact, when this amino acid is substituted with an alanine residue, p66Shc-mediated cell death is abrogated [4]. Moreover, it has been demonstrated that Endothelin-1 (ET-1), a vasoconstrictor peptide known to be a potent mitogen for glomerular mesangial cells (GMC), can trigger the phosphorylation of p66Shc on S36: p66Shc serine phosphorylation results in its association with the sequestering protein 14-3-3 [78]. Human and mouse S36 are found within the minimal S/TP (serine/threonine followed by proline) target motif that is recognized by MAPK (Mitogen Activated Protein Kinases), comprising ERKs (Extracellular signal Regulated Kinases), p38MAPK and JNKs (c-Jun N-terminal Kinases) [79,80].…”
Section: P66shc Is a Vertebrate Protein Conserved In Fishmentioning
confidence: 99%